Basic social biology and nest architecture of liostenogaster topographica turillazzi 1999 (Hymenoptera Stenogastrinae) - Hashim, Rosli; Turillazzi, S.; Baracchi, D.; Teseo, S. (2009)
The basic social biology and nest architecture of the social wasp Liostenogaster topographica Turillazzi 1999 were studied in Peninsular Malaysia. This species shows the main shared characteristics of hover wasps (Vespidae Stenogastrinae), including the use of an abdominal secretion in brood rearing and the presence on the nest of several females with developed ovaries. Colonies are small by the standards of social wasps but are probably the largest of any studied species of hover wasp. The nest has a peculiar architecture and the material used for its construction seems to be effective in keeping ants away from the perimeter of the nest.